Structural, blood flow and functional changes in the macular area and the expression of aqueous humor factors in myopia - Yang, Lu; Niu, Honglei; Sun, Wencui; Zhang, Dongchang; Li, Shuangnong; Hao, Shaofeng; Wang, Minting; Wang, Chuan; Hu, Junping; Li, Xian (Frontiers in Medicine, 2024)
Objective To compare the macular area parameters and aqueous humor factors between myopia and emmetropia. Methods Convenience sampling was used to select patients who visited the Changzhi Aier Eye Hospital’s department of ophthalmology from December 2018 to December 2022 as the study participants. They were divided into three groups according to whether they were diagnosed as mild myopia myopic, highly myopic or not as follows: the mild myopia group (60 cases, 108 eyes), the high myopia group (46 cases, 78 eyes) and the healthy emmetropia group (40 cases, 65 eyes). The differences in the macular integrity (MI) assessment, optical coherence tomography and optical coherence tomography angiography parameters and aqueous humor factors were compared between the three groups. Results AL in high myopia group was the highest, and that in emmetropia group was the lowest. The BCVA of mild myopia group was the highest. The RS in the high myopia group were significantly lowest in the three groups (26.42 ± 1.04 vs. 28.34 ± 0.76 vs. 31.92 ± 0.77) (F = 5.374, p = 0.013). The 63% BCEA, 95% BCEA and MI in the high myopia group were significantly highest (p < 0.05). The mean RPE thickness, mean CT and mean RT in the high myopia group were lowest (p < 0.05). The blood flow density were lowest in the superficial fovea, paracentral fovea and different subdivisions of the paracentral fovea in the high myopia group (p < 0.05). The VEGF concentration in the aqueous humor of the high myopia group was lowest (25.62 ± 17.43 vs. 32.45 ± 24.67 vs. 64.37 ± 21.14) (F = 9.237, p < 0.001). The MMP-2 concentration was highest (483 ± 201.48 vs. 410 ± 142.37 vs. 386 ± 154.34) (F = 5.542, p = 0.018). The VEGF concentration in the aqueous humor factor was negatively correlated with the AL in the myopia group (r = −0.438, p = 0.002), the MMP-2 concentration was positively correlated with the AL (r = 0.484, p = 0.010). Conclusion Patients with high myopia showed decreased retinal light sensitivity, fixation stability, superficial blood flow density and retinal thickness compared with people with emmetropia. A decreased VEGF concentration and increased MMP-2 concentration in the aqueous humor factor have potential associations with the development of high myopia.